Wyobraźnia wyzwolona. Kubistyczny model przekładu literackiego - Brzostowska-Tereszkiewicz, Tamara (Poznańskie Studia Polonistyczne. Seria Literacka, 2014)
The subject of the present discussion is the cubist model of literary translation, which assumes a multilateral perspective in simultanism, expressed in rotation of the original text through various historical timespaces, styles, poetics, conventions, registers, and varieties of an ethnic language (or several languages) in the field of target text, nullification of the oppositions between domestication and exoticisation, archaising and modernising, and maximisation of reader’s reception: reader’s multilingual and multicultural competences. The “eclipticity” of relation between source and target text, peculiar to the cubist model, as well as the nonlinear (stereometric) approach to original, metonymic and juxtapositional translation technique, and ironic modality, all lead, in cubist translation, to the requirement of intertextual confrontation with the original, which is necessary of an assessment of scale, value, and range of a translation experiment.